Trade Between East and West Pakistan at World Prices, 1960/61-1969/70 (The Pakistan Development Review, 1973)
The costs and prices of the commodities traded between East and West Pakistan are an aspect of interwing trade. It has been argued that domestically produced goods often involved greater costs of production and higher prices and therefore imports from one region to the other have been higher priced than similar goods from overseas. However the extent of the price differential between the domestic and world market varies from( commodity to commodity because of the unequal degree of protection or subsidy given by the Government. In other words the implicit exchange rate is not the same for all commodities and it differs considerably between different goods.